Genotypic Variability Analysis of Lotus (Nelumbo nucifera Gaertn.) from Bangladesh using RAPD and SSR Markers (Plant Tissue Culture and Biotechnology, 2022)
Lotus (Nelumbo nucifera Gaertn.) is a perennial aquatic plant with high ecological, medicinal, ornamental, and economic value from the prehistoric times. Different types of genotypes of lotus found in Bangladesh which represent a great variability. However, investigations on the variability of the lotus at genetic level are insufficient and limited in Bangladesh. In the current study, fourteen samples of lotus were collected from six different locations of Bangladesh were subjected to molecular analysis using codominant Simple Sequence Repeats (SSRs), as well as, dominant Random Amplified Polymorphic DNA (RAPD) markers to estimate the genetic diversity, and to test the genetic basis relationships among the germplasm. Analysis of SSRs showed a moderate level of polymorphism which was 68.12% and Nei’s genetic distance was ranging from 0.0328 to 0.7598 showing a significant level of variation among the genotypes. The germplasm collected from Kapasia identified as different and superior among the morphotypes. Moreover, RAPD analysis showed 60.44% polymorphism and Nei’s genetic distance was ranging from 0.0600 to 0.5743 indicating a moderate level of variability where yellow lotus was identified as distinct. Two Neighbor-Joining dendrograms were constructed using UPGMA method in which the germplasm were clustered into two main clades with 55% genetic similarity level for both RAPD and SSR markers. The current study was successful in establishing an efficient method for evaluating the variation and the genetic marker system to be used to identify core N. nucifera accessions. The method also could further assist in designing of suitable strategic programs to preserve the core lotus gene pool.Plant Tissue Cult. & Biotech. 32(1): 77-87, 2022 (June)